The Diversity and Potential of Aquatic and Succulent Plants in Purwodadi Botanical Gardens: Keanekaragaman dan Potensi Tumbuhan Akuatik dan Sukulen di Kebun Raya Purwodadi - Syaifudin, Andang; Farih Salsabila Wibowo, Farda (Jurnal Sains dan Pendidikan Biologi, 2022)
Purwodadi Botanical Gardens is an ex-situ plant conservation area that has a collection of plants for conservation, research, education, tourism and environmental services. One of the activities in the exploration and plant collection section is the addition of plant collections by seeding the results of flora exploration that has been carried out. Aquatic plants themselves have a variety of beautiful types, shapes, colors of leaves and flowers. This aquatic plant also has ecological value in restoring environmental quality, especially in water pollution. This research study is about the potential and diversity of the Purwodadi Botanical Gardens. This research study on the potential and diversity of aquatic plants was carried out using descriptive observation methods, with direct observations in the field based on literature review sources in the Purwodadi Botanical Gardens. The results showed that there were several species of aquatic plants in the Purwodadi Botanical Gardens, namely Monocrobia hastata (water hyacinth), Pistia statores (apu wood), Lemna minor (catfish's eye), Nelumbo nucifera (seroja), Echonidorus cordifolius (sword of spades). The collection of succulent plants is Agave angustifolia, Agave tequilana, Sansaviera trivasciata (in-law's tongue), Octopus agave, Euphorbia resinifera (resin spurge), and Hylocereus undatus (White Dragon Fruit),. The conclusion from our research is that the diversity of aquatic and succulent plants in the Purwodadi Botanical Gardens shows that the aquatic ecosystem is maintained, so that it has the potential to be cultivated and utilized to avoid environmental pollution.